MAKSIMALISASI KEUNTUNGAN PADA USAHA BENSIN PREMIUM DAN PERTALITE MENGGUNAKAN METODE SIMPLEKS DAN POM-QM - Matheus Supriyanto Rumetna; Tirsa Ninia Lina (LPPM Poltek ST Paul, 2021)
Mr. Ruddy is one of the small business actors, namely retail gasoline sales which is located at Moyo Kilometer 13, Sorong City, West Papua. Along with business development accompanied by intense competition, many problems arise and also affect the profits of this small business. Under these conditions, Mr. Ruddy must struggle to continue to carry out his business activities, especially production activities, so that business survival can continue. To maintain the continuity and development of the business, steps are needed to be able to allocate raw materials and increase profits. Therefore we need a method in determining the right combination, starting from the product made and the combination of the resulting product. The simplex method is part of a linear program and is very suitable for solving problems faced by Mr. Ruddy coupled with the use of information technology, namely the use of POM-QM tools to estimate the maximum profit obtained from each production made by gasoline sellers within one day quickly and precise, so that it has an accurate calculation estimate.